Pelatihan Pembuatan Sabun Cuci Tangan Herbal Sebagai Upaya Pemberdayaan Ekonomi Dan Kesehatan Masyarakat - Abu Bakar Betan; Rifqi Ferry Balfas; Yance R Rainuny; Rahmat Pannyiwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
The increasing number of environmentally-related infectious diseases and low handwashing habits are serious problems in densely populated communities. Furthermore, the use of readily available local herbal ingredients such as lemongrass, aloe vera, and pandan leaves has not been maximized as a source of income for the community. This community service activity aims to improve community skills and knowledge through training in making safe, hygienic, and economically valuable herbal hand soap. The training was conducted with 45 housewives and Family Welfare Movement (PKK) cadres in Village X. The implementation method included health education on Clean and Healthy Living Behaviors (PHBS), herbal soap-making demonstrations, group practice, production assistance, and pre- and post-training knowledge evaluations. The results showed a significant increase in participants' knowledge about the benefits of herbal plants, hand hygiene, and soap-making techniques. The average knowledge score increased from 56.7 to 88.4 in the post-test. Furthermore, 93% of participants were able to make soap independently and expressed interest in turning it into a business product. This activity effectively improved economic skills while supporting clean living behaviors through the use of herbal soap.